NGAL is downregulated in oral squamous cell carcinoma and leads to increased survival, proliferation, migration and chemoresistance - Monisha, J.; Roy, N.; Padmavathi, G.; Banik, K.; Bordoloi, D.; Khwairakpam, A.; Arfuso, Frank; Chinnathambi, A.; Alahmadi, T.; Alharbi, S.; Sethi, G.; Kumar, Alan Prem; et al. (MDPI AG, 2018)
Oral cancer is a major public health burden worldwide. The lack of biomarkers for early diagnosis has increased the difficulty in managing this disease. Recent studies have reported that neutrophil gelatinase-associated lipocalin (NGAL), a secreted glycoprotein, is upregulated in various tumors. In our study, we found that NGAL was significantly downregulated in primary malignant and metastatic tissues of oral cancer in comparison to normal tissues. The downregulation of NGAL was strongly correlated with both degree of differentiation and stage (I–IV); it can also serve as a prognostic biomarker for oral cancer. Additionally, tobacco carcinogens were found to be involved in the downregulation of NGAL. Mechanistic studies revealed that knockdown of NGAL increased oral cancer cell proliferation, survival, and migration; it also induced resistance against cisplatin. Silencing of NGAL activated mammalian target of rapamycin (mTOR)signaling and reduced autophagy by the liver kinase B1 (LKB1)-activated protein kinase (AMPK)-p53-Redd1 signaling axis. Moreover, cyclin-D1, Bcl-2, and matrix metalloproteinase-9 (MMP-9) were upregulated, and caspase-9 was downregulated, suggesting that silencing of NGAL increases oral cancer cell proliferation, survival, and migration. Thus, from our study, it is evident that downregulation of NGAL activates the mTOR pathway and helps in the progression of oral cancer.